Ca2+-permeable AMPA receptor: A new perspective on amyloid-beta mediated pathophysiology of Alzheimer's disease. (January 2017) - Whitehead, Garry; Regan, Philip; Whitcomb, Daniel J.; Cho, Kwangwook
Abstract: α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs) are the primary conduits of excitatory synaptic transmission. AMPARs are predominantly Ca 2+ -impermeable in the matured excitatory synapse, except under certain circumstances. Growing evidence implicates the Ca 2+ permeability of AMPARs in the regulation of long-term synaptic plasticity and in the pathophysiology of several neurological disorders. Therefore, the Ca 2+ conductance of AMPARs may have both physiological and pathological roles at synapses. However, our understanding of the role of Ca 2+ permeable AMPARs (CP-AMPARs) in Alzheimer's disease is limited. Here we discuss insights into the potential CP-AMPAR mediated pathophysiology of Alzheimer's disease, including: 1. Ca 2+ -mediated aberrant regulation of synapse weakening mechanisms, and 2. neuronal network dysfunction in the brain. Consideration of CP-AMPARs as primary drivers of pathophysiology could help in understanding synaptopathologies, and highlights the potential of CP-AMPARs as therapeutic targets in Alzheimer's disease. This article is part of the Special Issue entitled 'Ionotropic glutamate receptors'.